Global patterns of dead fine root stocks in forest ecosystems. (10th April 2018) - Wang, Cunguo; Chen, Zhao; Brunner, Ivano; Zhang, Zhen; Zhu, Xianjin; Li, Jiandong; Yin, Hong; Guo, Wei; Zhao, Tianhong; Zheng, Xingbo; Wang, Shuqi; Geng, Zhenzhen; et al.
Abstract: Aim: Dead fine roots are crucial components of the carbon cycle in global forest ecosystems. Despite their importance, knowledge concerning geographical patterns of dead fine root pools (necromass) and factors influencing their dynamics remain scarce across the globe. Location: Global. Methods: We analysed 136 published case studies covering 169 forest sites located throughout the world to identify broad patterns of necromass and biomass (living fine root pools) and to determine the responses to climate, edaphic gradients and stand properties. Results: W‐shaped pattern of forest necromass with latitude, from the Southern Hemisphere via the equator to the Northern Hemisphere, was observed. Specifically, more necromass was found at both low (tropical forests) and high latitudes (boreal forests), whereas less necromass was found at mid latitudes (temperate forests), which is in line with patterns of carbon stocks in soils at the global scale. Broad‐leaf forests had greater necromass than needle‐leaf forests, and fine root necromass of the two forest types showed opposing trends in response to shifts in mean annual precipitation and different sensitivities to changes in mean annual temperature and edaphic properties (e.g. soil carbon/nitrogen ratio and pH). Necromass increased with soil organic layer thickness and stand age for both forest types. Main conclusions: The hemispheric symmetrical necromass distribution is likely determined by changes in environmental conditions across latitudes. Different responses of dead fine roots in broad‐leaf and needle‐leaf forests may be caused by their distinct allocation and accumulation of carbon in relation to climate and to edaphic and forest characteristics at the global scale. Our results have important implications for accurate quantification and modelling of forest ecosystem carbon stocks and cycles and for assessments of their sensitivity and stability in a changing climate.